Performance of Great Occurrence Modal Responses in Non-Linear Seismic Examination - Angeline, A; Ravindra Raj, B.Jose; Vijayasarathy, R (International Journal of Computer Sciences and Engineering, 2015)
Practical problems related with the non- linear straight numerical addition of the equations of gesture leads to the use of non- linear static pushover examination of structures. Pushover examination is getting popular due to its simplicity. Great occurrence incomes and nonlinear belongings may play an important role in stiff and/or uneven structures. The influence of progressive incomes in pushover examination is not completely developed. The performance of great occurrence modal responses in non- linear seismic examination of arrangements is not known. In this paper an attempt is made to study the performance of great occurrence modal responses in non- linear seismic examination of structures.